KOLABORASI TERHADAP KINERJA LOGISTIK DENGAN KAPABILITAS LOGISTIK SEBAGAI VARIABEL MEDIASI PADA PERUSAHAAN MANUFAKTUR - Muhammad, Akmal Aziz; Manurung, Harris; Widowati, Dorina (JOURNAL OF BUSINESS STUDIES, 2024)
This study aims to analyze the effect of collaboration on logistics performance mediated by capabilities in manufacturing companies. In this study, hypothesis testing and cross-sectional data collection were carried out. This research was conducted quantitatively by distributing questionnaires which resulted in 109 respondents with purposive sampling method. The data processing techniques used include validity test, reliability test, hypothesis testing using Smart PLS software. The results of this study are: (1) There is an effect of collaboration on logistics performance, (2) There is an effect of collaboration on capability, (3) There is an effect of capability on logistics performance, (4) There is an effect of collaboration on logistics performance through capability. From the results of the research that has been done, it is hoped that it can add important implications for manufacturing companies in improving logistics performance through collaboration practices.